Group reminiscence therapy interventions in non-clinical older adults: A systematic review - Eryilmaz, Ali; Yildirim, Emre; Kurtulus, Hacer Yildirim; Yildirim, Murat (MOSBY-ELSEVIER, 2025)
Reminiscence therapy has gained significant attention in the last decade, supporte1d by increasing evidence of its efficacy in enhancing psychosocial functioning in different populations. However, questions remain regarding this therapy, particularly about the feasibility of developing successful therapeutic interventions for non-clinical older adults. This systematic review aimed to provide evidence on the intervention contents of experimental studies using group reminiscence therapy in elderly individuals. A descriptive systematic review design was applied using the Web of Science database. Out of the 127 studies reviewed, only 26 examined reminiscence therapy interventions with non-clinical older adults. These studies revealed evidence regarding the positive impacts of reminiscence therapy on mental health and well-being outcomes, including depression, anxiety, stress, life satisfaction, happiness, and general health. Overall, the existing literature on the efficacy of reminiscence therapy in older adults is limited and much more research is required to understand the therapeutic interventions in this population. (c) 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Reminiscence therapy; Older adults; Intervention; Systematic review; LONG-TERM-CARE; INTEGRATIVE REMINISCENCE; SELF-ESTEEM; INSTRUMENTAL REMINISCENCE; DEPRESSIVE SYMPTOMS; LIFE SATISFACTION; DEMENTIA; PEOPLE; PSYCHOTHERAPY; FEASIBILITY; Geriatrics & Gerontology; Nursing